Nucleotide sequence analysis of a variant human T-cell leukemia virus (HTLV-Ib) provirus with a deletion in pX-I. - Ratner, L (1985)
A variant of human T-cell leukemia virus subgroup I (HTLV-I), designated HTLV-Ib, has been isolated from a transformed T-lymphocytic cell line established from a Zairian patient with adult T-cell lymphoma. A recombinant phage clone of the variant provirus, denoted lambda MC-1, hybridizes under high stringency to HTLV-I DNA probes, but 17 of 43 restriction enzyme sites differ from those of HTLV-I, 10 of them clustering within 1.5 kilobases in the env-pX region. Since this variant virus retains its capacity to transform T-cells in vitro, and since a pX product is suspected to be important in transformation, we have determined the nucleotide sequence of the entire pX region of this virus for comparison to the prototype HTLV-I. In addition, the region between the gag and pol genes, parts of the pol and env genes, and a portion of the U3 region of the long terminal repeat sequence were also analyzed. We noted 141 single-base-pair changes among 3,897 base pairs, which were relatively well distributed over those portions of the provirus that were examined. In addition, an 11-base-pair deletion was found which included the potential initiator ATG codon of the first open reading frame of pX (pX-I). The next potential initiator codon predicted by the sequence is followed by 10 codons and then a termination codon. An identical deletion was also demonstrated in the only provirus present in another cell line established from the same patient on a different occasion after transformation in vitro of normal human umbilical cord blood cells. These results indicate that pX-I is not required for transformation.